(untitled) (MAUSAM, 2001)
The Tiros Operational Vertical Sounder (TOVS) is a popular satellite sounding system. In this paper certain features of Indian northeast monsoon have been studied with the help of three years of TOVS data received through the satellite ground station located at the Regional Meteorological Centre, Chennai. The TOVS based latitudinal and longitudinal profiles of Outgoing Longwave Radiation (OLR) and Precipitable Water Vapour (PWV) were derived for various phases of northeast monsoon activity, over coastal and interior Tamilnadu and oceanic regions. These were consistent with the known spatial rainfall characteristics of northeast monsoon. The average vertical temperature profiles derived for the various phases of northeast monsoon for the different regions revealed that the lowest layer and upper troposphere are warmer and mid troposphere colder during active northeast monsoon compared to dry phase. The diurnal variation of OLR and PWV and the comparability of TOVS derived data with conventional upper air data and INSAT data have been briefly discussed.